AN ANALYSIS ON THE POLICY IMPLEMENTATION OF ANTIBACTERIAL RESISTANCE CONTROL AT THE HOSPITAL - Indriana, Nani; Adisasmito, Wiku Bakti B. (Journal of Indonesian Health Policy and Administration, 2018)
In order to control Antibacterial Resistance at the hospital in Indonesia, the Government of Indonesia established an Antibiotics Resistance Control Committee and issued a Regulation from the Ministry of Health, regulation no 8/2015 on an antibiotics resistance control program at the hospital. This is an investigation on the Antibacterial Resistance Control Program (ARCP) at the Hospital, which compares its implementation at a government hospital and a private hospital, Persahabatan Central General Hospital (CGH) and Bogor Indonesian Red Cross Hospital (BIRCH). This was a descriptive study with a qualitative analysis obtained through indepth interviews and documentary research. We discovered that the ARCP was implemented better at Persahabatan CGH compared to BIRCH. Problems include ineffective communication, limited resources, lack of an antibiotic guideline (at BIRCH), lack of coordination between organizations, lack of supervision from the government, and the lack of motivation to implement the policy. These issues can be solved by intensifying the socialization of the policy, conducting more workshops and trainings for private and government hospitals that has not received any, providing an incentive for them to implement the program, such as including ARC into hospital accreditation indicators, and clarifying the benefits of the program to the stakeholders.